Corporal and testicular biometry in wild boar from birth to 12 months of age - Paula, Tarcízio Antônio Rêgo de; Murta, Danillo Velloso Ferreira; Costa, Deiler Sampaio; Santos, Marcelo Diniz; Faria, Fábio José Carvalho (Revista Ceres, 2012)
The aim of this tudy was to evaluate corporal and testicular development in wild boars (Sus scrofa scrofa) from birth to 12 months of age, evaluating body weight, biometric testicular parameters, and gonadosomatic index. Thirty-nine male wild boars from a commercial farm licensed by IBAMA were used in the study. The animals were weighed and assigned to 13 experimental groups. The testes were recovered through unilateral orchiectomy, weighed on an analytical balance and measured for length, width and thickness. Body weight and testicular measures increased with the age, up to 12 months, and were more accelerated in the first and ninth months. Initially the testicular growth pattern, between zero and nine months, followed the body growth, and the gonadosomatic index varied from 0.07 to 0.09%. Between 9 and 11 months, the testicular growth was superior to the body growth, and the gonadosomatic index varied from 0.09 to 0.16%. Finally, after 11 months of age, testicular and body growth had a similar behavior. In conclusion, body weight, testicular biometry, and gonadosomatic index development accelerated in the ninth month.

Objetivou-se, com esta pesquisa, investigar o desenvolvimento testicular e corporal de javalis (Sus scrofa scrofa), do nascimento aos 12 meses de idade, avaliando-se, em cada faixa etária, o peso corporal, o desenvolvimento biométrico dos testículos e o índice gonadossomático (IGS). Utilizaram-se 52 javalis machos, provenientes de um criatório comercial, devidamente regulamentado pelo IBAMA. Os animais foram pesados e divididos em 13 grupos experimentais; os testículos foram coletados por orquiectomia unilateral e, em seguida, pesados em balança analítica e mensurados comprimento, largura e espessura. Os valores de peso corporal e as medidas testiculares foram crescentes, após o nascimento, sendo sua variação mais acelerada no primeiro mês e aos nove meses. Inicialmente, o padrão de crescimento testicular, do nascimento aos nove meses de idade, acompanhou o crescimento corporal e o índice gonadossomático variou de 0,07 a 0,09%. Em seguida, entre nove e 11 meses, o valor de crescimento testicular foi superior ao de crescimento corporal e o índice gonadossomático variou de 0,09 a 0,16%. Por fim, após os 11 meses de idade, os valores crescimento corporal e dos testículos voltaram a se comportar de forma semelhante. Conclui-se que o desenvolvimento do peso corporal, a biometria testicular e o IGS tiveram crescimento mais acelerado aos nove meses de idade.
Keywords: Body weight; Gonadosomatic index; Testicular development; Sus scrofa scrofa